An evaluation of alternative explanations for widespread cytonuclear discordance in annual sunflowers (Helianthus). Issue 1 (23rd August 2018) - Lee‐Yaw, Julie A.; Grassa, Christopher J.; Joly, Simon; Andrew, Rose L.; Rieseberg, Loren H.
Summary: Cytonuclear discordance is commonly observed in phylogenetic studies, yet few studies have tested whether these patterns reflect incomplete lineage sorting or organellar introgression. Here, we used whole‐chloroplast sequence data in combination with over 1000 nuclear single‐nucleotide polymorphisms to clarify the extent of cytonuclear discordance in wild annual sunflowers ( Helianthus ), and to test alternative explanations for such discordance. Our phylogenetic analyses indicate that cytonuclear discordance is widespread within this group, both in terms of the relationships among species and among individuals within species. Simulations of chloroplast evolution show that incomplete lineage sorting cannot explain these patterns in most cases. Instead, most of the observed discordance is better explained by cytoplasmic introgression. Molecular tests of evolution further indicate that selection may have played a role in driving patterns of plastid variation – although additional experimental work is needed to fully evaluate the importance of selection on organellar variants in different parts of the geographic range. Overall, this study represents one of the most comprehensive tests of the drivers of cytonuclear discordance and highlights the potential for gene flow to lead to extensive organellar introgression in hybridizing taxa.